2011
DOI: 10.3399/bjgp11x556272
|View full text |Cite
|
Sign up to set email alerts
|

Primary excision of cutaneous melanoma: does the location of excision matter

Abstract: Melanoma is diagnosed more quickly if primarily excised in primary care, but current guidelines discourage this. The reports of all melanomas excised in north-east Scotland between 1991 and 2007 were analysed for adequacy of excision. Reports were analysed blinded as to source. Of primary biopsies performed in primary care, 72.5% were reported as completely excised, compared with 69.7% of those performed in secondary care (P<0.612). The difference remained non-significant following adjustment for important con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…5,[8][9][10] On the other hand, studies employing larger series and where the risk of bias has been minimised by blinding the location of excision biopsy during quality rating, have found no significant difference. 6,12,13 Previous research has explored the relationship between who excises melanoma 1998. 25 The authors compared survival by the training background (dermatologist, plastic surgeon, or general surgeon) of the operators who had removed at least In this study, differences in survival between the GP-and the dermatologytreated groups were non-significant and the authors concluded that this was because the GP group was small and because most GPs performing skin surgery in the study area did so in close cooperation with the local dermatology department.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…5,[8][9][10] On the other hand, studies employing larger series and where the risk of bias has been minimised by blinding the location of excision biopsy during quality rating, have found no significant difference. 6,12,13 Previous research has explored the relationship between who excises melanoma 1998. 25 The authors compared survival by the training background (dermatologist, plastic surgeon, or general surgeon) of the operators who had removed at least In this study, differences in survival between the GP-and the dermatologytreated groups were non-significant and the authors concluded that this was because the GP group was small and because most GPs performing skin surgery in the study area did so in close cooperation with the local dermatology department.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…5,[8][9][10] In contrast, studies from North Wales and Northeast Scotland, the latter being the only one where research was conducted blinded to location of initial excision biopsy, found quicker diagnosis and no significant difference in incomplete excision for GP versus specialist biopsy. 6,11,12 To date, there have been relatively few studies that compare outcomes for patients with melanoma treated initially by different specialties; however, one study has suggested that dermatologists may achieve the best results. 13 Notably, however, in Australia, which has among the highest global incidence of cutaneous melanoma, most melanomas are biopsied initially by GPs in primary care, without compromising survival compared with the UK.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Further research by the same authors showed that melanoma excisions by GPs appeared to be of similar quality to those undertaken by specialists; there was no difference demonstrated between frequent and infrequent GP surgeons. 4 This article describes how GP minor surgery is taking place and they are removing pigmented lesions, despite national guidance that they should be referred to secondary care as GPs perform less well. 5 Registries, clinical audits, and surgery checklists are all tools used to improve quality and are relevant to GP minor surgery.…”
Section: Introductionmentioning
confidence: 99%
“…2 Of 1263 initial biopsies of cutaneous melanoma, 262 (20.7%) were performed in primary care. Most initial biopsies (245; 93.5%) were performed by excision as is recommended in current guidelines.…”
Section: New Evidencementioning
confidence: 99%